Error culture and its impact on rework: An exploration of norms and practices in a transport mega-project. (May 2022) - Love, Peter E.D.; Matthews, Jane; Ika, Lavagnon A.; Fang, Weili
Abstract: Rework has been and continues to be a problem during the construction of transport mega-projects. This article examines the error culture of an alliance that forms part of a transport mega-project to determine its effectiveness in mitigating rework. Our article reveals that an error management culture positively correlates with reducing rework and holds a divergent relationship with an error aversion culture. We further show a negative association between an error aversion culture and the ability to reduce rework. It is suggested that more can be done to reduce errors and rework despite the prevalence of a strong error management culture in practice. We thus call for an explicit focus on reducing negative error consequences and developing strategies to handle errors. The article argues that providing a psychologically safe work environment, understanding and focusing on what goes right, and coaching to ensure that learning is transferred from an individual to an organizational level can reduce rework. Our study is the first attempt to examine the homogeneity of error culture (i.e., how errors and their consequences are dealt with) in an alliance mega-project setting. In addition, it provides a new line of exploration to address the issue of rework. Highlights: Provides a new line of exploration to address the issue of rework in construction. Examines the error culture of a transport mega-project. Reveals error management culture positively correlates with reducing rework and holds a divergent relationship with an error aversion culture. Strategies improving error culture are identified.